A thermogravimetric analysis of lignin char combustion. (February 2019) - Farrokh, Najibeh Toloue; Suopajärvi, Hannu; Sulasalmi, Petri; Fabritius, Timo
Abstract: Understanding the combustion behavior is the basic requirement for a new resource to be used as an alternative fuel for the industrial design of the future plants. In this article, thermogravimetric analysis (TGA) of lignin char combustion in different heating rates (5, 10 and 15 ° C/min) was investigated. Extracted combustion indices showed increased weight loss rate, peak temperature and burnout temperature but no change in ignition temperature for all samples when the heating rate increased. Lignin chars containing higher volatile material illustrated higher combustibility through the low ignition and burnout temperatures. Kinetic parameters of lignin combustion were also obtained by the Coat-Redfern method in the first-order kinetic model. High combustibility of high volatile sample (L300: vol%=41) was also confirmed by its low activation energy which was 46.68 compared to 150.34 for L500 (vol%=18) and 174.37 kJ/mol for L650 (vol%=5.1). The pre-exponential factor was also measured to be 2.61E-01, 8.15E+06 and 1.21E+08 min-1for L300, L500 and L650 respectively.